POLYPHONY IN THE EGYPTIAN CONTEMPORARY ARABIC NOVEL (A CASE STUDY OF GUANTANAMO) - Hosseini, Abdollah; Eshkevari, Seyyed Adnan; Lisar, Hamid Alizadeh (PEOPLE: International Journal of Social Sciences, 2018)
Novel is one of the important written forms of the narrative fiction and due to being relatively long, creates a suitable atmosphere to bring different ideas and worldviews to the text and helps the writer mention different ideas and introduce different characters in the text. This paper aims at studying Guantanamo Novel by Youssef Ziedan, the famous Egyptian writer. The paper tries to apply Mikhail Bakhtin’s concept of polyphony to Guantanamo novel and depicts the existing features of polyphony in it. The findings show that in Guantanamo, if a voice expresses its ideas, other voices will agree or criticize it. However, with further consideration, it is understood that the voices of the American characters are dominant over the Muslim characters and even the protagonist of the play. One of the significant features of the polyphony is the existence of intertextuality throughout the text. The writer brings quotations of Quran, hadith, poems and news and historical points in the first two hundred pages of the novel. The strongest contrast is between the American and Islamic characters and is seen between Sarah Klaus as an American psychologist and the Sudanic-Egyptian character of the play who is the novel’s protagonist. Youssef Ziedan has been successful in creating a polyphonic novel by Using different narrative modes and techniques such as stream of consciousness, religious and historic intertextuality, poetic language, decentralization, disinterestedness in presenting the voices and worldviews of characters.